Potential of Rambutan-Honey Antioxidants in Reducing Malondialdehyde Levels and Regenerating Hepatocyte Cells in Isoniazid-Rats Induced - Yuslianti, Euis Reni; Ratwita, Welly; Koswara, Teja; Afra, Aldilla (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Hepatotoxicity induced by prolonged administration of antituberculosis drugs such as isoniazid (INH) is associated with the production of free radicals. Rambutan-honey, rich in catalase enzyme, flavonoids, and vitamin C, exhibits antioxidant and immunomodulatory properties. This study purpose to assess the effect of rambutan-honey on malondialdehyde (MDA) levels and hepatocyte cell numbers in INH-induced rats. The research method using in vivo experimental study with a randomized posttest-only control group design. Thirty Wistar rats were divided into five groups: negative control(G1), positive control(G2), and three groups treated with rambutan-honey at doses of 250 mg/kgBW(G3), 500 mg/kgBW(G4), and 1000 mg/kgBW(G5). MDA levels were measured using the TBARS method on days 15 and 23, while hepatocyte cell numbers were assessed through histopathological examination using Hematoxylin-Eosin. Data were analyzed using One-Way ANOVA followed by Post-Hoc test. This study revealed that rambutan-honey at doses of 250, 500, and 1000 mg/kgBW significantly reduced MDA levels compared to controls, with a simultaneous increase in hepatocyte cell numbers (p=0.001). The conclusion of this research is the potential of rambutan-honey as an antioxidant and hepatoprotective agent, possibly mediated by its flavonoid content, which may stimulate superoxide dismutase activity akin to catalase enzyme and vitamin C.